Ionising radiation increases permeability of endothelium through ADAM10-mediated cleavage of VE-cadherin - Kabacik, Sylwia (Oncotarget, 2017)
The association between ionising radiation (IR) exposure and risk of cardiovascular diseases (CVD) is well documented, but the underlying mechanism is still poorly understood. As atherosclerotic plaques are the most common cause of CVD, we investigated the effects of IR on one of the critical parameters for atherosclerotic plaque formation – endothelium permeability to macromolecules. We used endothelial cells from human coronary artery as a model of the endothelial layer. Our results show that exposure of this endothelial layer to IR increased its permeability to macromolecules of various sizes in a dose-dependent manner. Immunofluorescence analysis revealed disruption of cell junctions caused by decreased amounts of two junction proteins, one of which is vascular endothelial cadherin (VE-cadherin). The reduction in the level of this protein was not due to diminished transcription but to protein processing instead. We observed a radiation dose-dependent increase in the cleavage of VE-cadherin by ADAM10. This was not mediated through the canonical VEGF route but was instead accompanied by intra-cellular calcium release. Importantly, inhibition of ADAM10 activity rescued IR-induced permeability. Our observations demonstrate that exposure to IR activates ADAM10 to cleave VE-cadherin leading to augmented endothelium permeability; a feature that can lead to the development of atherosclerotic plaques and increase the risk of cardiovascular disease.